Recruitment of the major vault protein by InlK: a Listeria monocytogenes strategy to avoid autophagy. - Laurent Dortet; Serge Mostowy; Ascel Samba-Louaka; Edith Gouin; Marie-Anne Nahori; Erik A C Wiemer; Olivier Dussurget; Pascale Cossart (PLoS Pathogens)
L. monocytogenes is a facultative intracellular bacterium responsible for listeriosis. It is able to invade, survive and replicate in phagocytic and non-phagocytic cells. The infectious process at the cellular level has been extensively studied and many virulence factors have been identified. Yet, the role of InlK, a member of the internalin family specific to L. monocytogenes, remains unknown. Here, we first show using deletion analysis and in vivo infection, that InlK is a bona fide virulence factor, poorly expressed in vitro and well expressed in vivo, and that it is anchored to the bacterial surface by sortase A. We then demonstrate by a yeast two hybrid screen using InlK as a bait, validated by pulldown experiments and immunofluorescence analysis that intracytosolic bacteria via an interaction with the protein InlK interact with the Major Vault Protein (MVP), the main component of cytoplasmic ribonucleoproteic particules named vaults. Although vaults have been implicated in several cellular processes, their role has remained elusive. Our analysis demonstrates that MVP recruitment disguises intracytosolic bacteria from autophagic recognition, leading to an increased survival rate of InlK over-expressing bacteria compared to InlK(-) bacteria. Together these results reveal that MVP is hijacked by L. monocytogenes in order to counteract the autophagy process, a finding that could have major implications in deciphering the cellular role of vault particles.